The usefulness of trauma scoring systems to differentiate severity of life-threatening injuries in forensic reports - Şenavcı, Murat; Erel, Özlem (The Bulletin of Legal Medicine, 2022)
Objective: Our study was carried out in order to evaluate the trauma scores used for forensic trauma cases according to the recommended guidelines. In the report were trauma resulting in death or majör life threatening situation the trauma scoring system is used to compare the impact of the trauma on ones life threatening situation. Methods: In this study, forensic traumatologic reports of 1684 cases were examined. Results: Sensitivity 75.6%, selectivity 99.1% for AIS optimal cut point 3, sensitivity 72.6% for ISS optimal cut point 9, selectivity 99%, sensitivity 14.6 for RTS optimal cut point 7,0061, The selectivity was calculated as 99,7, the sensitivity for CRAMS optimal cut point 8 was 13.5%, the selectivity was 99.9%, for TRISS the most suitable cut point was 93.610, the sensitivity was 23.4% and the selectivity was 99.7%. Patient groups between 0-17 years; sensitivity 76.1% for AIS optimal cut point 3, selectivity 99.2%, ISS 75% for selective cut point 9, selectivity 99.2%, sensitivity for RTS optimal cut point 7.4745 83.3% , selectivity 85.9%, CRAMS optimal cut point 9 for sensitivity 87.5%, selectivity 86.8%, TRISS optimal cut point 98.95 for sensitivity 95.7%, selectivity 93.7%, PTS optimal The sensitivity for cut-off point 9 was 96.7%, and the selectivity was 97.3%. Conclusion: It was found that TRISS and PTS trauma scoring systems have benefits especially in terms of standardization, but should be approached carefully in terms of their limitations in order to determine the severity of the disease and the possibility of mortality in traumatized patients.